NEW DIAGNOSTIC CRITERIA IN COMPUTER SYSTEMS OF DIAGNOSTICS OF FUNCTIONAL CARDIOVASCULAR SYSTEM OF HUMAN - Martsenyuk, V. P.; Sverstiuk, A. S.; Varyan, N. V. (Medical Informatics and Engineering, 2012)
The new diagnostic criteria for the automatized cardiodiagnostics as the coefficients of the statistic assessment of synchronously registered cardiosignals in terms of trigonometric functions are analysed and suggested in the paper.